2011
DOI: 10.1371/journal.pone.0021958
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Specific Neutrophil Dysfunction Associated with Interferon-Stimulated Gene Expression in the Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a poorly understood condition with greater than 30% mortality. Massive recruitment of neutrophils to the lung occurs in the initial stages of the ARDS. Significant variability in the severity and duration of ARDS-associated pulmonary inflammation could be linked to heterogeneity in the inflammatory capacity of neutrophils. Interferon-stimulated genes (ISGs) are a broad gene family induced by Type I interferons. While ISGs are central to anti-viral immunity, the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The greater population of neutrophils in aged animals following challenge, independent of vaccination, suggests that neutrophils may contribute to the increased severity of SARS-CoV pathogenesis in the aged. A pathogenic role for neutrophils in infection has been demonstrated for other respiratory viruses, including influenza virus, suggesting conserved mechanisms of enhanced respiratory pathology in the aged (26,32).…”
Section: Discussionmentioning
confidence: 98%
“…The greater population of neutrophils in aged animals following challenge, independent of vaccination, suggests that neutrophils may contribute to the increased severity of SARS-CoV pathogenesis in the aged. A pathogenic role for neutrophils in infection has been demonstrated for other respiratory viruses, including influenza virus, suggesting conserved mechanisms of enhanced respiratory pathology in the aged (26,32).…”
Section: Discussionmentioning
confidence: 98%
“…As a control, neutrophils were also incubated in the same conditions solely with complete RPMI. Neutrophil necrosis was determined by the percent of total lactate dehydrogenase release using the Cytotoxicity Detection Kit (Roche) [31]. Apoptosis was quantified by immunoassay for cytoplasmic histone-associated DNA fragments (Roche) and reported as the percent of histone-bound DNA in a given sample relative to the level of histone-bound DNA detected in neutrophils in which apoptosis was induced by cycloheximide [31]; after cell lysis, this assay uniquely identifies soluble chromatin fragments that are characteristic of apoptotic cells.…”
Section: Methodsmentioning
confidence: 99%
“…High ISG expression has been linked to development of ARDS . Furthermore, it has been suggested that unregulated IFN responses contributed to development of immunopathology and severe disease following SARS‐CoV infection .…”
Section: Innate Immune Responsementioning
confidence: 99%